The Feasibility and Oncological Safety of Axillary Reverse Mapping in Patients with Breast Cancer: A Systematic Review and Meta-Analysis of Prospective Studies. - Chao Han; Ben Yang; Wen-Shu Zuo; Gang Zheng; Li Yang; Mei-Zhu Zheng (PLoS ONE)
Objective The axillary reverse mapping (ARM) technique has recently been developed to prevent lymphedema by preserving the arm lymphatic drainage during sentinel lymph node biopsy (SLNB) or axillary lymph node dissection (ALND) procedures. The objective of this systematic review and meta-analysis was to evaluate the feasibility and oncological safety of ARM. Methods We searched Medline, Embase, Web of science, Scopus, and the Cochrane Library for relevant prospective studies. The identification rate of ARM nodes, the crossover rate of SLN-ARM nodes, the proportion of metastatic ARM nodes, and the incidence of complications were pooled into meta-analyses by the random-effects model. Results A total of 24 prospective studies were included into meta-analyses, of which 11 studies reported ARM during SLNB, and 18 studies reported ARM during SLNB. The overall identification rate of ARM nodes was 38.2% (95% CI 32.9%-43.8%) during SLNB and 82.8% (78.0%-86.6%) during ALND, respectively. The crossover rate of SLN-ARM nodes was 19.6% (95% CI 14.4%-26.1%). The metastatic rate of ARM nodes was 16.9% (95% CI 14.2%-20.1%). The pooled incidence of lymphedema was 4.1% (95% CI 2.9-5.9%) for patients undergoing ARM procedure. Conclusions The ARM procedure was feasible during ALND. Nevertheless, it was restricted by low identification rate of ARM nodes during SLNB. ARM was beneficial for preventing lymphedema. However, this technique should be performed with caution given the possibility of crossover SLN-ARM nodes and metastatic ARM nodes. ARM appeared to be unsuitable for patients with clinically positive breast cancer due to oncological safety concern.